In situ degradation kinetics of 6 roughages and the intestinal digestibility of the rumen undegradable protein. (21st November 2018) - Li, Qiujin; Xue, Bai; Zhao, Yumei; Wu, Tianqi; Liu, Haichao; Yi, Xing; Sun, Cuicui; Wang, Zhisheng; Zou, Huawei; Yan, Tianhai
Abstract: Three ruminally fistulated Xuanhan steers weighting 312.5 (±23.85) kg were used to determine the kinetics of ruminal degradation of nutrients using in situ nylon bag technique, and a modified 3-step in vitro procedure was adopted to estimate intestinal digestibility of 16-h rumen undegradable protein (RUP) of maize cob (MC ), distillers grains (DG ), spent mushroom substrate (SMS ), starch residue of sweet potato (SRSP ), citrus pulp (CPP ), and rice straw (RS ). Samples were incubated for 0, 2, 6, 16, 24, 36, 48 and 72 h. Additional samples were incubated for 16 h in the rumen, and the residues from these bags were transferred to the nitrogen-free polyester bags for determination of intestinal digestibility in vitro. The highest DM disappearance at 6-h incubation was in SRSP ( P < 0.01), and that at 36, 48, and 72 h was in CPP ( P < 0.01). The lowest DM disappearance at 2- and 6-h incubation was in RS and SMS ( P < 0.01), and that at 36, 48, and 72 h incubation was in RS, MC, and DG ( P < 0.01). The lowest and greatest CP disappearance was in RS and DG, respectively, at all the incubation times ( P < 0.01). There was no difference ( P > 0.07) on CP disappearance between DG and MC at all the time points except for 16 and 24 h. NDF and ADF disappearance for SRSP was significantly higher ( P < 0.01) than other roughages at all the time points except for ADF at 72 h. The lowest NDF and ADF disappearance was in DG at all the time points ( P < 0.01) except 2 and 6 h. The effective degradability (ED ) of DM was the highest in CPP ( P < 0.01) and the lowest in MC and RS ( P < 0.01). The highest and lowest ED of CP was in DG and in RS ( P < 0.01), respectively. The ED of NDF was the highest in SRSP ( P < 0.01), followed by CPP and RS, and the lowest in DG ( P < 0.01). The ED of ADF was the highest in SRSP and CPP ( P < 0.05), and the lowest in DG ( P < 0.01). For MC, DG SMS, SRSP, CPP, and RS, the intestinal digestibility of RUP was 95.28%, 37.23%, 38.72%, 48.06%, 54.49%, and 37.88%, respectively, and the content of intestinal digestible crude protein (IDCP ) was 23.65, 83.63, 35.63, 15.03, 25.60, and 12.03 g/kg, respectively. Distillers grain was considered to be of good quality for the greatest content of IDCP. Although not readily degraded in rumen, CP in MC may be digested well in small intestine.